INTERPRETASI SIMBOL DALAM NOVEL GUGUR BUNGA KEDATON KARYA WAHYU HARYONO (KAJIAN HERMENEUTIKA PAUL RICOEUR) - Astriana, Astriana; Anshari, Anshari; Hajrah, Hajrah (Fakultas Bahasa dan Sastra Indoensia, 2025)
This study aims to interpet cultural symbols in the novel Gugur Bunga Kedaton by Wahyu Haryono using Paul Ricoeur’s hermeneutic approach, which involves three step: understanding symbols, interpreting their meaning, and reflecting on their significance. This qualitative descriptive research analysis data in the form of words, phrases, or clauses found in the novel. Data collection was conducted using reading and note-taking method. The data analysis technique involved data reduction, data presentation, and verification or conclusion drawing. The result indicate that cultural symbols reflect human activities, including ideas, action and artifacts such as kanuragan, semedi, Sanghyang Kamahayanikan, wahyu keprabon, sowan, kungkum, sirep Megananda, and serat geguritan. these symbols represent the cultural life of the Majapahit and Demak Kingdom in the 15th-16th centuries, while also revealing hidden meanings within their social and cultural context.